Self-Assembled Hydrogel Membranes with Structurally Tunable Mechanical and Biological Properties - Abdel-Rahman, Rasha M; Abdel-Mohsen, A M; Frankova, Jana; Piana, Francesco; Kalina, Lukas; Gajdosova, Veronika; Kapralkova, Ludmila; Thottappali, Muhammed Arshad; Jancar, Josef (Biomacromolecules, 2024)
Using supramolecular self-assembled nanocomposite materials made from protein and polysaccharide components is becoming more popular because of their unique properties, such as biodegradability, hierarchical structures, and tunable multifunctionality. However, the fabrication of these materials in a reproducible way remains a challenge. This study presents a new evaporation-induced self-assembly method producing layered hydrogel membranes (LHMs) using tropocollagen grafted by partially deacetylated chitin nanocrystals (CO-g-ChNCs). ChNCs help stabilize tropocollagen's helical conformation and fibrillar structure by forming a hierarchical microstructure through chemical and physical interactions. The LHMs show improved mechanical properties, cytocompatibility, and the ability to control drug release using octenidine dihydrochloride (OCT) as a drug model. Because of the high synergetic performance between CO and ChNCs, the modulus, strength, and toughness increased significantly compared to native CO. The biocompatibility of LHM was tested using the normal human dermal fibroblast (NHDF) and the human osteosarcoma cell line (Saos-2). Cytocompatibility and cell adhesion improved with the introduction of ChNCs. The extracted ChNCs are used as a reinforcing nanofiller to enhance the performance properties of tropocollagen hydrogel membranes and provide new insights into the design of novel LHMs that could be used for various medical applications, such as control of drug release in the skin and bone tissue regeneration.
Keywords: Chitin; pyridiny; nanokompozity; iminy; Cell Line, Tumor; biokompatibilní materiály; Imines; Fibroblasts; Nanocomposites; Nanoparticles; chitin; lidé; Hydrogels; Drug Liberation; fibroblasty; nanočástice; mechanické jevy; Humans; Biocompatible Materials; Membranes; léky s prodlouženým účinkem; Delayed-Action Preparations; Pyridines; hydrogely; konformace proteinů, alfa-helix; Mechanical Phenomena; Protein Conformation, alpha-Helical; Tropocollagen; uvolňování léčiv; nádorové buněčné linie; membrány; tropokolagen